Criminalistics counteraction to corruption displays: problems and prospects - Khlus, Alexander M. (Journal of the Belarusian State University. Law, 2019)
In the article an author is analyse factors corruptions, simultaneously examined scientists and as its reasons. The short-story analysis of some fundamental, legal, organizational-economic, informative, social and cultural and historical factors (reasons) of corruption allowed to draw conclusion, that they make the of the same name groups of terms for an origin corruption as the negative social phenomenon. It is thus noticed that not all these terms are characteristic for any state. Depending on the device of the state, sizes of his territory, features of national culture and legislation and other circumstances forming of one or another terms is possible for a corruption. As reason of corruption an author sees a circumstance, reflecting essence maintenance of arising up between people relations, formed on a mutual benefit, on the basis of principle of mutual exchange «I give, that and you gave». On the basis of this principle there are corruption relations. It is possible to examine the relations of bribery proof of this fact. An author specifies on the role of criminalistics in an exposure and removal of terms of corruption. One of functions of this science is prognostication of development of criminal activity. With the purpose of exposure of terms of corruption criminalistics prognostication must be carried out in the process of leadthrough of examination of normative legal acts. By methods which it is expedient to use during the leadthrough of such examination there are a criminalistics analysis and matrixing.
Keywords: corruption; factors of corruption; terms of corruption; reasons of corruption; principle of mutual exchange; corruption relations; criminalistics; criminalistics prognostication; examination of normative legal acts; criminalistics analysis; criminalistics matrixing